Um Modelo de Inovação Bottom Up: Museu de Favela - Nakano, Natalia [UNESP]; Jorente, Maria José Vicentini [UNESP] (My University, 2013)
This article aims to present, describe and discuss the innovation model of the first territorial open-air museum, designed in a favela in Rio de Janeiro, the Favela Museum (MUF). The concepts of slums, traditional museum and ecomuseums differentials are introduced in order to contextualize the universe MUF is inserted. Moreover, the paper discusses the concept of territorial open-air museum collection and how curatorship takes place this context, as well as the possible forms of interaction with the diversity of individuals served by a museum such as MUF. Furthermore, the role of this new museum typology in society is discussed, entities created by bottom up innovation initiative undertaken by MUF into the new museology of action. It concludes with considerations about the shift of focus on the role played by MUF as agent of social and cultural development.

Este artigo tem como objetivo apresentar, descrever e discutir o modelo de inovação do primeiro museu territorial ao ar livre, concebido em uma favela no Rio de Janeiro, o Museu de Favela (MUF). Nele são introduzidos os conceitos de favela, e diferenciados museu tradicional e os ecomuseus, a fim de contextualizar o universo do MUF. Discute-se o conceito de coleção de um museu territorial ao ar livre e como se dá o trabalho de curadoria nesse contexto, bem como os tipos de interação possíveis com a diversidade de indivíduos atendidos por um museu como o MUF. Discute-se ainda o papel dessa nova tipologia museológica na sociedade, a partir de entidades criadas pela inovação do tipo bottom up realizada pela iniciativa do MUF dentro da nova museologia de ação. Conclui-se com considerações a respeito da mudança de foco do papel desempenhado pelo MUF como agente de desenvolvimento social e cultural.
A bottom up initiative model: Museu de Favela